Imaging in Acute Stroke - New Options and State of the Art - Anders Fogh Christensen (Frontiers Research Topics, 2018)
One in six suffers a stroke during their lifetime and stroke remains the major cause of new onset disability in adulthood. The worldwide burden of stroke is increasing due to an ageing population, however, globally haft of stroke victims are young. Stroke is the clinical diagnosis of an acute vascular incident and covers a multitude of pathophysiological causes. The clinician needs imaging to make decisions on acute treatment as well as to plan a secondary prevention strategy: a non-contrast CT and a Duplex of the carotids followed by an aspirin as a one size fits all strategy does not always provide sufficient support for those decisions. Presently, fast, generally available, and non-invasive imaging provides new possibilities of establishing a cause of stroke, provide specific information on the brain parenchyma - including possibly salvageable tissue and micro-bleeds - as well as allowing for more specific prognostication in acute stroke. This eBook covers both ischemic and haemorrhagic stroke and includes hot topics such as micro-bleeds, salvageable tissue and spot-sign, clinically challenging issues including movement artefacts in MRI as well as an overview of present options including pragmatic and feasible suggestions for an approach to state of the art acute imaging.